Correlation of Aloe Vera-Based Liquid Organic Fertilizer with Growth Traits of Oil Palm (Elaeis guineensis Jacq.) - Umar Husein Abdullah; Ruhalena Wilis; Elviani; Nurlia Farida; Khairun Nisa (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Aloe vera gel contains various secondary metabolites that contribute to the plant’s beneficial properties. This study employed a correlation analysis test to investigate the relationship between Aloe vera LOF dosage and S.H, S.D, and NL in Oil Palm Seedlings (Elaeis guineensis Jacq.). This study was conducted in a controlled experimental garden managed by the Plantation Management Study Program at the Politeknik Indonesia Venezuela, located in Cot Suruy Village, Ingin Jaya District, Aceh Besar Regency. The study was conducted from March to July 2025. The garden temperature was maintained between 25°C and 28°C. Data analysis was carried out using SPSS 25 software. To see the correlation analysis between LOF, SH, SD, and NL in Oil Palm Seedlings (Elaeis guineensis Jacq.), a bivariate CA was used. The use of Aloe vera LOF at various doses (100–400 ml) was proven to have a significant effect on the vegetative growth of oil palm seedlings, especially on PH, SD, and NL. Aloe vera LOF, as a natural leaf fertiliser, can provide a significant positive effect on the vegetative growth of oil palm seedlings by increasing the height, diameter, and NL simultaneously.